Experimental study of coal and gas outburst processes influenced by gas pressure, ground stress and coal properties - Ou, Jianchun; Wang, Enyuan; Li, Zhonghui; Li, Nan; Liu, He; Wang, Xinyu (Frontiers in Earth Science, 2023)
With the continuous increase of mining depth, coal and gas outburst poses a significant threat to mining safety. Conducting research on the mechanisms of coal and gas outbursts contributes to understanding the evolutionary process of such incidents, thus enabling accurate prediction and prevention of coal and gas outbursts during mining operations. This paper has developed a comprehensive visual experimental system that is specifically tailored to simulate diverse coal body conditions, ground stress and gas pressures. By monitoring and analyzing the real-time progression of coal fissures during the outburst process, we can obtain valuable insights into the evolution and mechanisms of coal and gas outbursts. Additionally, this study introduces a method to determine the critical threshold for predicting coal and gas outbursts, and the critical gas pressure threshold for Jiulishan Mine is established at 0.6 MPa.